Web3 toolkits: A user innovation theory of crypto development - Darcy W.E. Allen; Jason Potts (Journal of Open Innovation: Technology, Market and Complexity, 2023)
The development of Web3 — a stack of decentralised technologies underpinned by blockchains — isn’t simply a technical or financing challenge, it is also a problem of innovation and entrepreneurial discovery. In this paper we apply the lens of user innovation toolkit theory to the development of Web3. Toolkits are an organizational design solution to an innovation problem with sticky and local information. Our aim is to explore how toolkits theory applies to Web3 innovation, proposing that Web3 innovation is being organized through toolkits (e.g., blockchains, token standards, DAO frameworks) that enable efficient organization of sticky information to facilitate innovation. The contribution of this paper is the first application of toolkits theory to Web3, reframing its development as a problem of entrepreneurship and innovation in the context of distributed information. We provide implications for the role of developers as user innovators, the economic problem of emergent toolkit stacking, and the design of toolkit business models.